Three Layers of Uncertainty: an Experiment - Ilke Aydogan; Loϊc Berger; Valentina Bosetti; Ning Liu (Fondazione Eni Enrico Mattei (FEEM), 2018)
We experimentally explore decision-making under uncertainty using a framework that decomposes uncertainty into three distinct layers: (1) physical uncertainty, entailing inherent randomness within a given probability model, (2) model uncertainty, entailing subjective uncertainty about the probability model to be used and (3) model misspecification, entailing uncertainty about the presence of the true probability model among the set of models considered. Using a new experimental design, we measure individual attitudes towards these different layers of uncertainty and study the distinct role of each of them in characterizing ambiguity attitudes. In addition to providing new insights into the underlying processes behind ambiguity aversion -failure to reduce compound probabilities or distinct attitudes towards unknown probabilities- our study provides the first empirical evidence for the intermediate role of model misspecification between model uncertainty and Ellsberg in decision-making under uncertainty.
Keywords: D81; 330; Ambiguity Aversion; Reduction of Compound Lotteries; Non-expected Utility; Model Uncertainty; Model Misspecification